The Effectiveness of Using The Application of Pegadaian Digital Service to Easy Customer Transaction at Pegadaian Cirebon Branch - Sutarjo, Moh; Nurlia, Titim (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2022)
The Pegadaian Digital Service application is a Pegadaian digital service in the form of a mobile-based application that can provide Pegadaian product services to make it easier for customers to make transactions anytime and anywhere. However, there are still many customers who carry out conventional transactions. This is the background for researchers to choose the title